Decree Of The President Of The Arab Republic Of Egypt No. 69 Of The Year 2015 = قرار رئيس جمهورية مصر العربية رقم 69 لسنة 2015 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic